Pengaruh Customer Relationship Management Terhadap Loyalitas Konsumen di Cold n' Brew: (The Influence of Customer Relationship Management Towards Customer Loyalty in Cold n’ Brew) - Rizqi Maharani Prestasyawati; Minar Ferichani; Nuning Setyowati (UPT Penerbitan Universitas Jember, 2021)
The purpose of this study was to analyze the effect of Customer Relationship Management on customer loyalty in Cold n’ Brew. The population in this study were customers of Cold n’ Brew in Surakarta. Using Purposive sampling, the sample in this study was 1000 respondents. The analysis in this study is Partial Least Square (PLS) with Smart PLS 3.0. The results showed that process variables, human resources, and data and information technology had a positive effect on consumer loyalty in Cold n 'Brew. The results showed that process variables, human resources, and data and information technology had a positive effect on consumer loyalty in Cold n ‘Brew.